SISTEM INFORMASI PUBLIKASI ILMIAH DOSEN DARI GOOGLE SCHOLAR BERBASIS WEB - Widianto, Eko Didik; Najich, Zakky Ainun; Eridani, Dania (Jurnal Sistem Komputer, 2021)
In the rapid development of industry era, managing jobs from aÂ  project have been so conveniently done. Recently, managers who create a project can follow up (to finish and to report) online. Furthermore, developers who receive that task either want to finish and report their task for their manager easily and immediately. The benefit that makes this process much easier is the whole activities can be done with the use of smartphones. In its implementation, managers give tasks for developers without knowing that the developers can do them in time or not. Therefore, this paper proposes the development of a Project Management application where every developer. The development of this application aims to make sure that a project finishes on time. This application can be of a platform to collect proofs of finished projects, as an upload function is available. This function enables users to collect files such as photo, document, or pdf.